Komposisi Mikroorganisme Pada fermentasi Umbi Ubi Kayu Pahit Menjadi â€œWikau Maomboâ€ - Nurhayani H., Muhiddin (Fakultas MIPA UNM, 2011)
The aim of the research was to know total count of microorganisms and character of group of type mikroorganisme which natural grow of during fermentation process of